Development of an early diagnostic tools for anaerobic granulation bioreactor for industrial wastewater treatment - Chen, Jun Guo. (2010)
Performance of anaerobic expanded granular sludge bed bioreactor is dependent on the concentration and bioactivity of biomass, which is closely linked to the biogas production of the granular sludge. Parameters of importance include pH, ionic strength, temperature, inhibitor concentration, etc. The working characteristics of granular sludge could easily be deteriorated during periods of shock load, operational failure or presence of inhibitor, etc. As a result, the biomass flush-out would occur and this could lead to system failure. Thus, there is a need to develop a simple, straight forward protocol that is sensitive and rapid to correct the operating condition in the reactor before collapse of the bacterial consortium. The objective of this study was to determine the bioactivity of anaerobic biomass when exposed to possible phenol during the continuous operation of an industrial wastewater treatment plant. With the information obtain from both batch and continuous operation, it is possible to formulate an optimal protocol to counter periods of shock loads.